Copper improves the anti-angiogenic activity of disulfiram through the EGFR/Src/VEGF pathway in gliomas. Issue 1 (1st December 2015) - Li, Yi; Fu, Shi-Yuan; Wang, Li-Hui; Wang, Fang-Yang; Wang, Nan-Nan; Cao, Qi; Wang, Ya-Ting; Yang, Jing-Yu; Wu, Chun-Fu
Highlights DSF potently inhibited angiogenesis both in vitro and in vivo. Cu improves the anti-angiogenic ability of DSF both in vitro and in vivo. DSF/Cu suppresses VEGF secretion through EGFR/c-Src/VEGF pathway.